Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1074/jbc.m414610200
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anions Are Involved in Mediating the Effect of Low K Intake on c-Src Expression and Renal K Secretion in the Cortical Collecting Duct

Abstract: It is well known that K restriction suppresses renal K excretion (2). This is achieved, at least in part, by decreasing the apical K conductance in the cortical collecting duct (CCD) 1 and by stimulating K absorption in the outer medullary collecting duct (3, 4). However, the mechanism by which low K intake suppresses the apical K channels is not completely understood. We previously demonstrated that low K intake increased the expression of Src family protein tyrosine kinase (PTK) such as c-Src and c-Yes (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…The AngII-induced PTK-independent reduction of ROMK channel activity presumably reflects other PKC-associated effects on the channel, such as that regulated by phosphatidylinositol 4,5-bisphosphate (PIP 2 ) (26). Of note was our observation that application of PMA to HA-treated CCDs failed to inhibit the ROMK channel (data not shown), suggesting that PTK is required for activation of PKC (27,28 anions, reduces expression of cSrc in CCDs, which increases ROMK channel activity and potassium excretion in LK rats (30). The immunodetection of components of NADPH oxidase in the CCD suggests that NADPH oxidase may be a source of intracellular ROS in this nephron segment (31).…”
Section: Resultsmentioning
confidence: 93%
“…The AngII-induced PTK-independent reduction of ROMK channel activity presumably reflects other PKC-associated effects on the channel, such as that regulated by phosphatidylinositol 4,5-bisphosphate (PIP 2 ) (26). Of note was our observation that application of PMA to HA-treated CCDs failed to inhibit the ROMK channel (data not shown), suggesting that PTK is required for activation of PKC (27,28 anions, reduces expression of cSrc in CCDs, which increases ROMK channel activity and potassium excretion in LK rats (30). The immunodetection of components of NADPH oxidase in the CCD suggests that NADPH oxidase may be a source of intracellular ROS in this nephron segment (31).…”
Section: Resultsmentioning
confidence: 93%
“…The observation that the addition of H 2 O 2 increased the expression of the P110␣-subunit suggests that increases in superoxide anions and related species are partially responsible for the stimulation of PI3K expression induced by low K intake. Also, we previously demonstrated that low K intake increases superoxide anion levels, which stimulate the expression of Src family PTK (2). Thus this suggests that increases in superoxide anion levels induced by low K intake are responsible for stimulation of expression of PI3K and PTK.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Next, we explored the role of superoxide anions in mediating the effect of low K intake on the expression of ING4 because K restriction increases the level of superoxide in the renal tubules (4). We examined the effect of K restriction on ING4 expression in rats treated with tempol, an agent that decreases superoxide production in the kidney (4) and other tissues (13).…”
Section: Low K Intake Stimulates Ing4 Expression By a Superoxide-depementioning
confidence: 99%
“…Low K intake has been shown to activate ERK, p38 MAPK, and Src family PTK, which inhibit ROMK channel activity (4,5). Therefore, we examined whether expression of ING4 stimulates the phosphorylation of p38 and ERK in Xenopus oocytes.…”
Section: Ing4mentioning
confidence: 99%
See 1 more Smart Citation